The Effect of a Regimen of Antifungal Cream Use on Episodes of Acute Adenolymphangitis (ADL) among Lymphedema Patients: An Application Using Marginal Structural Models - K.E. Mues; M. Klein; D.G. Kleinbaum; W.D. Flanders; L.M. Fox (Springer, 2018)
Episodes of adenolymphangitis (ADL) are a recurrent clinical aspect of lymphatic filariasis (LF) and a risk factor for progression of lymphedema. Inter-digital entry lesions, often found on the web spaces between the toes of those suffering from lymphedema, have been shown to contribute to the occurrence of ADL episodes. Use of antifungal cream on lesions is often promoted as a critical component of lymphedema management. Our objective was to estimate the observed effect of antifungal cream use on ADL episodes according to treatment regimen among a cohort of lymphedema patients enrolled in a morbidity management program. We estimated this effect using marginal structural models for time varying confounding. In this longitudinal study, we estimate that for every one-unit increase in the number of times one was compliant to cream use through 12 months, there was a 23% (RR = 0.77 (0.62, 0.96)) decrease in the number of ADL episodes at 18 months, however the RR's were not statistically significant at other study time points. Traditionally adjusted models produced a non-significant RR closer to the null at all time points. This is the first study to estimate the effect of a regimen of antifungal cream on the frequency of ADL episodes. This study also highlights the importance of the consideration and proper handling of time-varying confounders in longitudinal observational studies.